2011
DOI: 10.1094/pdis-11-10-0799
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pseudoperonospora cubensis Sporangia in Commercial Cucurbit Fields in Michigan

Abstract: Granke, L. L.. and Hausbeck, M. K, 2011, Dynamics of Pseudoperonospora cubensis sporangia in commercial cucurbit fíelds in Michigan. Plant Dis. 95:1392-1400.Major outbreaks of cucurbit downy mildew have been observed since 200.5 in Michigan, the top state for pickling cucumber production in the United States. Airborne concentrations of Pseudoperotwspora ctibensis sporangia were monitored from 2006 to 2009 in a commercial cucurbit field in each of five Michigan counties. Temperature, relative humidity, leaf wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
(37 reference statements)
5
9
2
Order By: Relevance
“…Spores were detected on 70 to 80% of days sampled in our study, which was within the range of days (42 to 100%) during which spores were detected in the previous Michigan study in commercial, managed fields (9). Spores were detected on 70 to 80% of days sampled in our study, which was within the range of days (42 to 100%) during which spores were detected in the previous Michigan study in commercial, managed fields (9).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Spores were detected on 70 to 80% of days sampled in our study, which was within the range of days (42 to 100%) during which spores were detected in the previous Michigan study in commercial, managed fields (9). Spores were detected on 70 to 80% of days sampled in our study, which was within the range of days (42 to 100%) during which spores were detected in the previous Michigan study in commercial, managed fields (9).…”
Section: Discussionsupporting
confidence: 80%
“…A previous spore trapping study in commercial cucurbit fields in Michigan also found that spores were trapped within 4 days of spore sampling initiation when sampling started in June (9). In this study, airborne P. cubensis sporangia were detected in mid-May, prior to cucumber being planted in the field and within 5 days of spore trapping initiation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Typical of most downy mildew organisms, aerial concentration of P. cubensis spores above the crop canopy exhibits a diurnal periodicity (Figure 3) with peak concentrations occurring between 0800 and 1000 h (36,70). The pathogen is a prolific producer of spores and can produce up to 2 × 10 8 spores/ha in a day (70).…”
Section: Sporangia Production and Escapementioning
confidence: 99%
“…The structure and information content of disease hazard warnings issued by the CDM ipmPIPE are characteristic of predictive systems that typically have sustained use in disease management (32). At the field scale, direct detection and estimation of airborne inoculum have also found a role in disease hazard warnings and scheduling of fungicide applications (33,36,37). In Michigan, sporangia characteristic of P. cubensis have been detected within days of field plantings (37).…”
Section: Detection and Elimination Of Primary Inoculummentioning
confidence: 99%